Antibiotics for treating scrub typhus. - Panpanich R. (2014)
BACKGROUND: Scrub typhus is a bacterial disease in regions of Asia and the Pacific. Antibiotics (chloramphenicol, tetracycline, and doxycycline) have been used to treat the disease. Resistance to these antibiotics has been reported. OBJECTIVES: To evaluate antibiotic regimens for treating scrub typhus. SEARCH STRATEGY: We searched the Cochrane Infectious Diseases Group specialized trials register (March 2002); the Cochrane Controlled Trials Register (The Cochrane Library, Issue 1, 2002); MEDLINE (1966 to March 2002); EMBASE (1988 to January 2002); LILACS (2001, 40a Edition CD-ROM). We checked references and contacted authors for additional data. SELECTION CRITERIA: Randomized and quasi-randomized studies comparing antibiotic regimens in people diagnosed with scrub typhus. DATA COLLECTION AND ANALYSIS: One reviewer screened the search results; both reviewers assessed eligibility, quality and extracted data. We used Review Manager (Version 4.1), and expressed results as Relative Risk (binary) or weighted mean difference (continuous), with 95% confidence intervals. MAIN RESULTS: Four trials involving 451 adults met the inclusion criteria. One small study did not demonstrate a difference between tetracycline with chloramphenicol (participants afebrile after 48 hours, Relative Risk 1.00; 95% confidence interval 0.07 to 15.26). Two small trials did not show a difference between doxycycline and tetracycline (participants afebrile after 48 hours, Relative Risk 0.46; 95% confidence interval 0.12 to 1.75). One trial showed rifampicin to be more effective than doxycycline (for eliminating fever, Relative Risk 0.41; 95% confidence interval 0.22 to 0.77; no relapses in either group). REVIEWER'S CONCLUSIONS: Limited data has not demonstrated a difference between tetracycline and doxycycline. Limited data suggest rifampicin is effective in areas where scrub typhus appears to respond poorly to standard anti-rickettsial drugs.